Prevalence and molecular characterization of multidrug resistant Campylobacter isolated from animals and humans as a one health approach - Mohamed Kholeif; Mohamed G. Sayed; Ahmed Fotouh; Doaa. A. Abd-Allah; Rania M. Ewida; Ahmed R. Elbestawy; Nehal K. Alm Eldin; Mohamed S. Diab (Scientific Reports)
Abstract Campylobacteriosis is a significant zoonosis with major public health implications. This study aimed to investigate the prevalence, molecular characteristics, and antimicrobial resistance of Campylobacter spp. in animal (rectal swabs and milk), environmental (fecal, water, and wall swabs), and human samples (stool and hand swabs) in New Valley Governorate, Egypt. Among 573 samples analyzed, Campylobacter spp. prevalence was highest in rectal swabs (32.9%) and human stool samples (74.2%), with lower rates in fecal samples (25.9%), milk (25.7%), wall swabs (13.1%), and water (10%). All isolates showed 100% resistance to clindamycin, while being completely sensitive to imipenem and amikacin. Multidrug resistance was found in 90.1% of the isolates, and 16S rRNA was detected in 90% of randomly selected Campylobacter spp. The hipO, cadF, and ceuE genes were detected in 77.8%, 33.3%, and 22.2% of the isolates, respectively. Phylogenetic analysis of the 16S rRNA gene showed significant congruence either between the tested isolates and each other or with other isolates in the gene bank, confirming the zoonotic transmission of multi-drug-resistant Campylobacter spp. This highlights the urgent need for improved biosecurity on farms, better food handling practices, and heightened public health awareness to mitigate the risk of Campylobacteriosis.